An investigation into the relationship between type-2 FOU size and environmental uncertainty in robotic control - Benatar, Naisan; Aickelin, Uwe; Garibaldi, Jonathan M. (2012)
It has often been suggested that when faced with large amount of uncertainty in situations of automated control type-2 fuzzy logic based controllers will out perform the simpler type-1 varieties due to the latter lacking a mechanism to model this uncertainty and adapt accordingly. This paper aims to investigate this problem in detail and analyse when and the magnitude by which a type-2 controller will improve upon type-1 performance. A sailing robot is subjected to several experiments in which the uncertainty and the complexity of the sailing problem is gradually increased in order to observe the effects on measured performance. Improved performance is observed, however this does not occur in all cases. The size of the FOU is shown to be very important in the creation of the type-2 system with potentially severe performance penalties for incorrectly sized systems.